Whole-body integration of gene expression and single-cell morphology - Martínez Vergara, Hernando; Pape, Constantin; Meechan, Kimberly; Zinchenko, Valentyna; Genoud, Christel; Wanner, Adrian A.; Mutemi, Kevin Nzumbi; Titze, Benjamin; Templin, Rachel M.; Bertucci, Paola Y.; Simakov, Oleg; Dürichen, Wiebke; et al. (Cell, 2021)
Animal bodies are composed of cell types with unique expression programs that implement their distinct locations, shapes, structures, and functions. Based on these properties, cell types assemble into specific tissues and organs. To systematically explore the link between cell-type-specific gene expression and morphology, we registered an expression atlas to a whole-body electron microscopy volume of the nereid Platynereis dumerilii. Automated segmentation of cells and nuclei identifies major cell classes and establishes a link between gene activation, chromatin topography, and nuclear size. Clustering of segmented cells according to gene expression reveals spatially coherent tissues. In the brain, genetically defined groups of neurons match ganglionic nuclei with coherent projections. Besides interneurons, we uncover sensory-neurosecretory cells in the nereid mushroom bodies, which thus qualify as sensory organs. They furthermore resemble the vertebrate telencephalon by molecular anatomy. We provide an integrated browser as a Fiji plugin for remote exploration of all available multimodal datasets.